The impact of financial market stress on financial performance in China - Belkhir, Nadia (Journal of Posthumanism, 2025)
This study investigates the impact of financial market stress on corporate financial performance in the Chinese economic environment over the period from January 2016 to April 2025. Employing multiple linear regression models, this study evaluates the marginal effects of key global financial stress indicators including the S&P 500, VIX, WTI crude oil prices, the RTS Index, and silver prices, on corporate performance metrics in China. Results indicated that U.S. market indicators did significantly impact corporate performance in China, whereas the Russian RTS index had no statistical significance. Although the results demonstrated the relevance of global financial conditions for emerging financial markets, they could explain only a limited amount of variance. The relatively weak performance of the explanatory model seems to suggest that some important local factors were omitted. These findings offer important insights for investors, regulators, and policymakers seeking to enhance financial stability and corporate performance amid evolving economic and financial uncertainties in China.